Attentional dysfunction arises from right frontocentral and occipital network connectivity in Parkinson's disease - Isobel Timothea French; Kuo-Hsuan Chang; Wei-Kuang Liang; Wen-Sheng Chang; Yen-Shi Lo; Yi-Ru Wang; Mei-Ling Cheng; Norden E. Huang; Hsiu-Chuan Wu; Siew-Na Lim; Chiung-Mei Chen; Chi-Hung Juan (NeuroImage: Reports)
Background: The Flanker task measures visuospatial attention and assesses the attentional network by distinguishing pathways for enhancing information at attended regions and suppressing information at unattended ones (Kopp et al., 1996). In Parkinson's disease (PD), the attentional network is impaired due to dysfunctional fronto-subcortical circuits connected to the basal ganglia, disrupting response selection and inhibition. While electroencephalography (EEG) may reveal abnormalities of these circuits in PD, dynamic brain oscillations critical for interareal communications cannot be deciphered with conventional time-frequency analyses. Objective: To utilize the novel Holo-Hilbert Spectral Analysis (HHSA) to reveal dynamic EEG features of the Flanker task in PD patients and healthy normal controls for differentiating and elucidating attentional network deficits in patients. Methods: The novel HHSA was applied to uncover nonlinear features of the Flanker task EEG and to analyse connectivity using phase-amplitude cross-frequency coupling. Results: Holo-Hilbert transform (HHT) results showed an attenuated midfrontal theta (FMθ) in the congruency effect in PD patients, consistent with past studies. HHSA showed a loss of low-frequency amplitude modulations (fam) in the theta carrier frequency band (fc) during the congruency effect in PD. Importantly, connectivity analyses using the Holo-Hilbert cross-frequency phase clustering (HHCFPC) revealed a loss of theta-gamma cross frequency coupling (CFC) from the right prefrontal cortex to other frontal and contralateral regions. Decrements were also shown in PD patients from right frontal cortical to occipital areas in theta-beta CFC. Conclusions: These visuospatial attention deficits of PD revealed with the advanced analytical method of the HHSA and HHCFPC may inaugurate further neurophysiological biomarkers for cognitive function evaluation in PD and related movement disorders.